2020
DOI: 10.3390/biology9080191
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Senescence Bystander Effect: The Role of Exosomes

Abstract: Ionizing Radiation (IR), especially at high doses, induces cellular senescence in exposed cultures. IR also induces “bystander effects” through signals released from irradiated cells, and these effects include many of the same outcomes observed following direct exposure. Here, we investigate if radiation can cause senescence through a bystander mechanism. Control cultures were exposed directly to 0, 0.1, 2, and 10 Gy. Unirradiated cells were treated with medium from irradiated cultures or with exosomes extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Some cytokines may also act as mediators of bystander response, such as TNF-alpha, IL-8, and TGF-beta. This senescence-associated secretory phenotype (SASP) could induce paracrine senescence through DNA damages and arrest cells in G0/G1 phase 52 . DNA damage detection may cause cells to leave the cell cycle or undergo apoptosis, consequently not to reproduce irreparably damaged chromosomes 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Some cytokines may also act as mediators of bystander response, such as TNF-alpha, IL-8, and TGF-beta. This senescence-associated secretory phenotype (SASP) could induce paracrine senescence through DNA damages and arrest cells in G0/G1 phase 52 . DNA damage detection may cause cells to leave the cell cycle or undergo apoptosis, consequently not to reproduce irreparably damaged chromosomes 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Our second aim was to investigate the effects of the EVs secreted by irradiated SH-SY5Y cells on proliferation, migration, and response to IRs. An autocrine EVs stimulating effect has been already reported in other tumor cell lines and in cancer patients [ 36 , 37 ]. We found that in SH-SY5Y cells, EVs10 stimulated proliferation, in line with what has been reported in different cell lines [ 34 ], although this effect has not been observed in all tumor cells [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 91%
“…An important finding was that EV-mediated effects were durable, and 3 months after EV treatment, cell depletion kinetics of most cell subpopulations (with the exception of MSCs and HSPCs) resembled effects seen in directly irradiated mice 3 months after irradiation. Other in vitro studies also reported EV-mediated long-term radiation-induced bystander effects [ 49 ]. Thus, we hypothesize that EVs isolated within 24 h of irradiation transmit signals which are able to induce acute cellular damage resembling direct irradiation.…”
Section: Discussionmentioning
confidence: 98%
“…Arscott et al observed increased abundance of EVs of human normal astrocytes after exposure to 4Gy [ 46 ]. In primary fibroblasts, Elbakrawy et al found that EV secretion peaked 1 h and 24 h following irradiation [ 49 ]. Furthermore, it was demonstrated by Cagatay et al that various organs (brain, heart, liver) and plasma have an increased rate of EV secretion 1 day and 15 days after total or partial body irradiation with 2Gy [ 50 ].…”
Section: Discussionmentioning
confidence: 99%